On the efficacy of separating control and data into different frequency bands - Kyasanur, Pradeep; Padhye, Jitendra; Bahl, Paramvir; Bahl, Victor; Padhye, Jitu (2005)
Radio spectrum allocated for use in unlicensed wireless networks is distributed across non-contiguous frequency bands. Existing MAC protocols, like IEEE 802.11, operate only in contiguous bands. We propose a split-channel protocol that improves the capacity of infrastructure and multi-hop wireless networks by utilizing a sliver of unused spectrum in the lower frequency band for control purposes. The proposed Control Channel-based MAC Protocol (C2M) increases the throughput by moving the contention resolution overheads to a separate low rate channel. We allow simultaneous channel contention and data transmission by incorporating advance reservation on the control channel, and data aggregation on the data channel. Simulation results show that compared to IEEE 802.11, C2M significantly improves network performance. Finally, we discuss the potentially large benefits of extending C2M to networks with directional antennas.